A Category “Public Order” and Limitations on Party Autonomy in Contracts for the Carriage of Passengers by Sea - Аракелян, Мінас Рамзесович; Аракелян, М. Р.; Аракелян, Минас Рамзесович; Arakelian, Minas R.; Іванова, Дар’я Андріївна; Іванова, Д. А.; Иванова, Дарья Андреевна; Ivanova, Daria A.; Туляков, Вячеслав Олексійович; Туляков, В. О.; Туляков, Вячеслав Алексеевич; Tuliakov, Viacheslav O. (Publishing house Helvetica Limited liability company, 2021)
This article attempts to research the purpose, the meaning and the essence of the category “public order” in the legal regulation and practice of law enforcement in the sphere of passengers’ sea shipping. In the first part of the article, the authors consider the role of the public (imperative) element in the legal regulation of passengers’ sea shipping. It is paid attention to the significant segment of the state and the supranational administrative regulation in the modern legal basis of such shipping. It gets a manifestation in consolidating the possibilities of imperative influence on the system of private legal relations, including relations, complicated by a foreign element, particular on the sphere of passengers’ sea shipping. In the second part of the article, the authors applied to the definition of the correlation connections of the category “public order” with the related legal categories “law and order”, “civil order”, “world order”, made the distinction between the categories “order” and “regime”. It is emphasized the attention on the legal regime is a process aimed at establishing public order. The third part of the article is devoted to brief research of the international public order in the projection on the problems of passengers’ sea shipping. It is laid emphasis on the attempt of the world community to form a legal basis for countering illegal actions in the maritime spaces that violate the established international public order, aimed at reservation and protecting health and lives of people. It is noted that the sphere of human rights allows emphasizing more clearly the limits of the institute “public order”, which remains underestimated in the Ukrainian doctrine of international private law. Finally, the authors examine the public order clause as one of the leading institutes of the international private law and the relevant legislation of most modern states. It is emphasized the lack of a definition of the category of “public order” under the conditions of the proper regulation in the laws of the relevant clause.

У цій статті здійснена спроба дослідження мети, значення та суті категорії “публічний порядок” у правовому регулюванні та практиці правозастосування у сфері морських перевезень пасажирів. У першій частині статті автори розглядають роль публічного (імперативного) елемента у правовому регулюванні морських пасажирських перевезень. Звертається увага на вагомий сегмент державного та наддержавного адміністративного регулювання у сучасному правовому базисі таких перевезень. Воно отримує прояв у закріпленні можливостей імперативного впливу на систему приватноправових відносин, у т.ч. відносин ускладнених іноземним елементом, зокрема на сферу морських пасажирських перевезень. У другій частині статті автори звернулися до визначення кореляційних зв’язків категорії “публічний порядок” із суміжними правовими категоріями “правопорядок”, “громадський порядок”, “cвітовий правопорядок”, здійснили розмежування категорій “порядок” та “режим”. Акцентували увагу на тому, що правовий режим є процесом, спрямованим на встановлення публічного порядку. Третю частину статті присвячено короткому дослідженню міжнародного публічного порядку у проекції на проблематику морських пасажирських перевезень. Наголошується на спробі світового співтовариства сформувати правову основу для протидії незаконним діям у морських просторах, які порушують встановлений міжнародний публічний порядок, якого спрямовано на збереження та охорону здоров’я та життя людей. Зазначається, що сфера прав людини дозволяє чіткіше підкреслити межі інституту “публічний порядок”, що залишається недооціненим в українській доктрині міжнародного приватного права. Нарешті, автори розглядають застереження про публічний порядок як один з провідних інститутів міжнародного приватного права та відповідного законодавства більшості сучасних держав. Підкреслюється відсутність визначення категорії “публічний порядок” за умов належної регламентації у законодавствах відповідного застереження.
Arakelian M. A Category “Public Order” and Limitations on Party Autonomy in Contracts for the Carriage of Passengers by Sea / M. Arakelian, D. Ivanova, V. Tuliakov / Lex Portus. – Vol. 7. - Issue 4. - Publishing house Helvetica Limited liability company, 2021. – P. 28–56.
Keywords: sea shipping; passengers; public order; clause; imperative norms; super-imperative norms; морські перевезення; пасажири; публічний порядок; застереження; імперативні норми; надімперативні норми; Research Subject Categories::LAW/JURISPRUDENCE